PENGARUH DAN SIMULASI SIMPANG JL. ABDULLAH DAENG SIRUA- JL. ADHYAKSA BARU DI KOTA MAKASSAR MENGGUNAKAN SOFTWARE PTV VISSIM 9.00 - Muslimin, Eviliona; -, Rudi; Umar, Indriani (Universitas Bina Taruna Gorontalo, 2023)
In this study to determine the effect and simulation of traffic engineering performance at the intersection of Jalan Abdullah Daeng Sirua Barat -Abdullah Daeng Sirua Timur -Adhyaksa Baru using the PTV VISSIM 9 software during the extension of the curfew during the Covid-19 pandemic and during the implementation of restrictions on community activities. (PPKM) level 4 (four). By using the field survey method for 5 working days with primary and secondary data collection then data processing with MKJI theory and simulated using PTV Vissim 9.00 software. From the results of the research, the intersection does not fulfill the capacity of the road due to the large volume of traffic that passes through the intersection. vehicle (noise).